Positive infusion of propofol drug during induction - Syam, Syafiie; Rami, Mustapha Ait; Tadeo, Fernando (IEEE, 2010)
Non-opioid intravenous anesthetic agents, such as propofol, have been used in anesthesia since 1970’s for conscious sedation. In this paper, the study aims to regulate the syringe pump of propofol infusion during induction. The syringe pump is regulated by using a linear positive controller. The controller is designed so as to satisfy positivity in state. The control output is positive and bounded. Effect site concentration is used as a feedback to the controller. Simulation results show that the controller regulates propofol very well and the BIS responses of the patient are observed so that there is no overshoot or oscillation.